Red eminence : The intermediate-luminosity red transient AT 2022fnm - Moran, S.; Kotak, R.; Fraser, M.; Pastorello, A.; Cai, Y.-Z.; Valerin, G.; Mattila, S.; Cappellaro, E.; Kravtsov, T.; Gutiérrez, C. P.; Elias-Rosa, N.; Reguitti, A.; et al. (EDP Sciences, 2025)
We present results from a five-month-long observing campaign of the unusual transient AT 2022fnm, which displays properties common to both luminous red novae (LRNe) and intermediate-luminosity red transients (ILRTs). Although its photometric evolution is broadly consistent with that of LRNe, no second peak is apparent in its light curve, and its spectral properties are more reminiscent of ILRTs. It has a fairly rapid rise time of 5.3 ± 1.5 d, reaching a peak absolute magnitude of −12.7 ± 0.1 (in the ATLAS o band). We find some evidence for circumstellar interaction, and a near-infrared excess becomes apparent at approximately +100 d after discovery. We attribute this to a dust echo. Finally, from an analytical diffusion toy model, we attempted to reproduce the pseudo-bolometric light curve and find that a mass of ∼4 M⊙ is needed. Overall, the characteristics of AT 2022fnm are consistent with a weak stellar eruption or an explosion reminiscent of low-energy type IIP supernovae, which is compatible with expectations for ILRTs.